Energy efficiency in green building to achieve company sustainability - Chen, Min Ann; Abu al-Rejal, Hussein Mohammed (2015)
Energy efficiency is the key to achieve sustainability in green building.Lowering the energy consumption in construction is starting to become a significant improvement chance for many organizations.This research will identify the benefits of energy efficiency, explore the methods to apply efficient energy usage in green building, and explore the obstacles in attaining energy efficiency in green building.Even though green buildings use a lesser amount of energy compare with usual building, energy efficiency still hard to achieve, due to some barriers to put into practice energy efficiency.This study will interview a property development company in Malaysia.After analysis, energy efficiency contributed two main benefits in the company such as reduced greenhouse gases emission and lower the air pollution problem, and energy saving.The company implemented electrical feeding and sensor system in lighting system, passive design, and cross ventilation to achieve energy efficiency in their development projects.However, cost barrier, information barrier, and outdoor condition and climate barrier are the obstacles in attaining energy efficiency practices. Due to the time constrain, this research only able to interview one company.With the aim of getting more accurate result, should be interview more companies in the future research because of the energy efficiency cover a wide area in the construction field.